The impact of shyness on social anxiety among college students: Mediating role of regulatory emotional self-efficacy and resilience - Yue Wang; Yuan Zhao (PLoS ONE, 2026)
Background Social anxiety is prevalent among college students, and shyness has been consistently linked to elevated social anxiety. However, the psychological mechanisms underlying this association remain insufficiently understood. This study examined whether regulatory emotional self-efficacy and resilience mediate the association between shyness and social anxiety among Chinese college students. Methods This study employed the Cheek and Buss Shyness Scale, Regulatory Emotional Self-Efficacy Scale, 10-item Connor-Davidson Resilience Scale, and Interaction Anxiousness Scale to survey 1,012 college students from three universities in Shandong, Anhui, and Jiangsu provinces. Pearson correlation analysis and PROCESS Macro Model 6 regression analysis were used to examine the relationships among shyness, regulatory emotional self-efficacy, resilience, and social anxiety. Result Shyness was positively associated with social anxiety. Resilience significantly mediated this association. In addition, shyness was indirectly associated with social anxiety through the sequential pathway of regulatory emotional self-efficacy and resilience. However, regulatory emotional self-efficacy alone did not independently mediate the relationship. Conclusion These findings suggest that resilience plays a central role in the association between shyness and social anxiety, and that regulatory emotional self-efficacy may function indirectly through resilience. Interventions targeting resilience and regulatory emotional self-efficacy may help reduce social anxiety among shy college students.